Morbidity pattern and hospital outcome of neonates admitted in secondary care level hospital in Bangladesh (Mymensingh Medical Journal, 2009)
Mymensingh Med J. 2009 Jul;18(2):136-41.The abstract of this article is available on the PubMed website